Silence - Endo, Shusaku, 1923-1996. (New York [N.Y.] : Taplinger Pub. Co., 1980)
Sustained by dreams of glorious martyrdom, a seventeenth-century Portuguese missionary in Japan ministers to the outlawed Christians until Japanese authorities capture him and force him to watch the torture of his followers, promising to stop if he will renounce Christ.
The story of a seventeenth-century Portuguese priest in Japan at the height of the persecution of the Christian community.
Includes bibliographical references.
Translation of: Chinmoku.
Keywords: Christians -- Japan -- Fiction; Missionaries -- Japan -- Fiction; Persecution -- Japan -- Fiction; Japan -- Civilization -- 17th century -- Fiction; Japan -- History -- 16th century -- Fiction